Pure yolk sac tumor of sacrococcygeal region - Rashim Sharma; Sudeep Khera; Arvind Sinha; Taruna Yadav (University of São Paulo, 2021)
The sacrococcygeal region is the most common site for the extragonadal germ cell tumors comprising seminomatous and non-seminomatous tumors. Seminomatous tumors are seminomas, and non-seminomatous tumors comprise mainly teratoma (mature and immature), yolk sac tumor (YST), embryonal carcinoma (EC), and choriocarcinoma. These tumors occur in newborns, infants, and adolescents. Other common sites for extragonadal germ cell tumors are the brain and mediastinum, although they may occur anywhere in the body. These tumors may occur in mixed as well as pure form. So, sectioning from different areas should be done before labeling them as pure germ cell tumors. YST, in its pure form, is rare and therefore should not be missed as it is chemosensitive. The patient should be thoroughly assessed clinically. Imaging also becomes necessary while evaluating swelling in the sacrococcygeal region and can aid in differentials. When the clinical and imaging suspicion of either Sacrococcygeal teratoma or other germ cell tumor is high, serum biomarkers as alfa-fetoprotein should be requested. The serum levels are necessary and should be done preoperatively, postoperatively, and during the course of chemotherapy as follow-up. However, the final diagnosis rests on the histopathological diagnosis. We report one such case of pure YST in the sacrococcygeal region in a 9-month-old female child. The imaging suggested sacrococcygeal teratoma type 4, and high alfa-fetoprotein levels were determined postoperatively.